1998
DOI: 10.1002/(sici)1097-0274(199805)33:5<493::aid-ajim9>3.0.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

Impact of managers' personal determinants in notifying workplace hazards

Abstract: Notification about work hazards is a legal requirement in advanced industrial countries, but workers have claimed, that in many cases, they do not receive enough information regarding risks, exposure, and medical problems. The recent professional literature on the subject has explored the ways in which notification is delivered without suffıciently considering the psychological incentives and barriers that may affect managers in transmitting risk information. The present study aimed at examining managers' pers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…By applying a six-level framework of training outcomes, we were able to illustrate that studies of super- A major drawback of these studies is the lack of attention to the importance of self-efficacy as a factor known to shape behavioral intentions and performance of safety-related behavior among supervisors. 74 The belief in one's own competence seems to be the critical link between supervisors' understanding of the ergonomic risks in the workplace and their ability to redesign work environment elements and work practices. Notably, an earlier meta-analysis found insufficient evidence for the effectiveness of ergonomic training in changing workers' knowledge and attitudes and strong evidence for behavioral outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…By applying a six-level framework of training outcomes, we were able to illustrate that studies of super- A major drawback of these studies is the lack of attention to the importance of self-efficacy as a factor known to shape behavioral intentions and performance of safety-related behavior among supervisors. 74 The belief in one's own competence seems to be the critical link between supervisors' understanding of the ergonomic risks in the workplace and their ability to redesign work environment elements and work practices. Notably, an earlier meta-analysis found insufficient evidence for the effectiveness of ergonomic training in changing workers' knowledge and attitudes and strong evidence for behavioral outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…A few investigators have explored the relationship between managers' and employees' beliefs about workplace health and safety. For example, Rabin et al found that employees are more likely to report receiving information about workplace hazards when managers hold more positive outcome beliefs and have more confidence about helping others [ 23 ]. Parker et al found that employee self-reported safe behaviour is associated longitudinally with supportive supervision, job autonomy and the quality of communication about their job [ 24 ].…”
Section: Discussionmentioning
confidence: 99%